Social abandonment, injustice and forgetfulness: the northeast brazilian’s identity and the hinterland in the works of Graciliano Ramos and Antônio Torres - Preto Souza, Alisson (2020)
Regarded as a study about minorities, Vidas Secas, by Graciliano Ramos, and Essa Terra, by Antônio Torres were compared seeking to comprehend the oppression of the northeast Brazilians’ identity. For this research, we read theories of representation of Hall (2006) and Cassirer (1992); the literary study Temposfuturos of Reis (2012); the study about the fiction and history of Brazil’s draught of Scoville (2011); the definition of counterculture proposed by Pereira (1986); and, at last, the identitary questions in Torre’s fiction of Preto-Souza (2019). Using images left in the cannon such as the draught and the poverty of Vidas Secas, the fiction of Torres can be understood as countercultural, as it problematizes the current system and the political status quo of the hinterland at the end of the 20th century. The work’s results showed that, while Graciliano bets on the silence and the draught, converging to the formation of the northeast Brazilian’s mythology and denouncing the political corruption and the institutional abandonment, Torres highlights the forgetfulness of the northeast cultural identity, among other social problems like xenophobia and exile related to the them.